ATLANTIS-II (Cruise 102) Preliminary CTD Data from JASIN 1978. - Pennington ,Nancy; Briscoe,Melbourne G (1979)
102 Profiles of conductivity, temperature, and depth (pressure) (CTD) were taken in the JASIN area northwest of Scotland in July-September 1978. These stations consisted od single and yo-yo profiles. The data set includes 14 stations taken near Anton Dohrn Seamount at 57 deg 30 min N, 11 deg W. Plotted profiles of temperature, salinity, sigma-theta, and buoyancy frequency, and a listing of the data, are included for most stations. (Author)